The Effect of Mini Modules on Parents' Knowledge of the Importance of Play Therapy in Toddlers During Hospitalization at Rsud Rupit Muratara Regency in 2023 - Liviana, Nanik; Samidah, Ida; Handayani, Tita Septi (Universitas Dehasen Bengkulu, 2024)
Hospitalization is a plan that requires children to stay in the hospital to undergo therapy and treatment. During this process children can experience traumatic and stressful. Most children who experience hospitalization show uncooperative behavior towards health workers shown by crying reactions. playing games will release children from the tension and stress they experience because by playing games, children will be able to divert their pain to the game. The type of research is Quasi Experimental, with a research design of One Group pre test and post test design. Sample 58 people. Structured mini-modules were given to every mother whose child was treated at Rupit Hospital. Questionnaires were given to respondents to assess the level of knowledge. Data analysis using Paired T-test parametric test. The average knowledge of respondents before being given a mini module is 54.7 and after being given a mini module to 71.21, with p < α = 0.05 with knowledge (p = 0.000). From these results it is concluded that there is an effect of giving mini modules about play therapy during hospitalization on knowledge. It is expected that the Rupit Hospital can provide a special room for play and play programs for children.